Regulation of the intestinal immune system by flavonoids and its utility in chronic inflammatory bowel disease - Hoensch, Harald Peter; Weigmann, Benno (World Journal of Gastroenterology, 2018)
Flavonoids are phytochemicals which can regulate the activity of the intestinal immune system. In patients with chronic inflammatory bowel disease (IBD) there is an overexpression and imbalance of the components of the inflammatory immune reactions which are chronically activated. Suppression of inflammation can be achieved by anti-inflammatory drugs which are used in clinical medicine but these can cause serious side effects. Flavonoids can have natural immunosuppressive properties and inhibit the activation of immune cells and its effectors (chemokines, TNF-, cytokines). Phytochemicals such as flavonoids bind to the nuclear Ah (aryl hydrocarbon) -receptor thereby stimulating protective enzyme activities. As shown by clinical evidence in patients and by experimental work some flavonoids (apigenin, epigallocatechin gallate) were effective in the inhibition of inflammation. Instead of or additionally to anti-inflammatory drugs flavonoids can be used in IBD patients to treat the over-reactive immunologic system. This is accomplished by upregulation of the Ah-receptor. Flavonoids interact with toll-like receptors expressing on the surface of immune cells, then they were internalized to the cytosol and transferred into the nucleus, where they were attached to the Ah-receptor. The Ah-receptor binds to the Ah-R nuclear translocator and via Ah response element beneficial protective enzymes and cytokines are induced, leading to upregulation of the anti-inflammatory system.
EVALuna2:33882